INSTAGRAM STORIES DALAM AJANG PENGUNGKAPAN EKSISTENSI DIRI (STUDI KASUS SELEBGRAM @JIHANPUTRI) - Krismasakti, Bramayanti (Universitas Prof. Dr. Moestopo (Beragama), 2019)
In this research, author is doing research about the use of instagram stories as a self-existence arena (case study on @jihanputri). This research used a qualitative based approach with constructivism paradigm, and case study method. In collecting data, author used indepth interview and observation. So, the purpose of this research is to find out the use of instagram stories as a self-existence arena which done by @jihanputri. Based on the research that has done by indepth interview and observation to the source, author found that @jihanputri used her instagram stories not only to communicate but also share information to her followers. While @jihanputri communicate to her followers more frequent, she gain more existence on people’s eyes.